Contractual Savings, Stock, and Asset Markets - Impavido, Gregorio; Musalem, Alberto R. (World Bank, Washington, DC, 2014)
The authors study the relationship between the development of insurance, and contractual savings, (the assets and portfolio composition of pension funds, and life and non-life insurance companies) and the development of stock markets (market capitalization and value traded). Their contribution lies in providing cross-country, and time-series on a hypothesis that is very popular - but had not been substantiated - among supporters of funded pension systems, and insurance in which reserves are largely invested in tradable securities (equities and bonds). The authors present a three-assets model (money, quasi money, and shares) to study the effects of the development of contractual savings (pension funds and life insurance companies) and non-life insurance companies on assets market equilibrium, and on stock market development. They use an unbalanced panel of 21 OECD, and 5 developing countries, and an error components two-stage least squares (EC2SLS) estimator, including a test for endogeneity of these institutional investors. The results support the hypothesis that contractual savings, and non-life insurance companies can be treated as exogenous to the development of stock markets; that contractual savings and non-life insurance companies, as well as their portfolio policies, promote stock market development as measured by stock market capitalization, and value traded as a share of GDP. The results show that stock market capitalization is positively correlated with the return on stocks, the assets of contractual savings and non-life insurance companies, the shares of stocks in the portfolios of contractual savings and non-life insurance companies, and the value traded stocks. Stock market capitalization is negatively correlated with the real interest rate, the real return on money (measured by the inverse of inflation), and stock market volatility. Stock market value traded is positively correlated with the shares of stocks in the portfolios of contractual savings and non-life insurance companies, and the real return on money. It is negatively correlated with the real interest rate. The authors conclude that insurance and contractual savings are powerful instruments for developing stock markets, providing depth and liquidity. Higher liquidity, in turn, further promotes market capitalization.